PERBAIKAN HASIL PENETASAN (DOC) AYAM KAMPUNG DENGAN MENGGUNAKAN BIBIT UNGGUL PADA PETERNAKAN DI DUSUN AIRLOUW KECAMATAN NUSANIWE AMBON - Papilaya, Bercomien J.; Labetubun, Jusak; Sarfan, Riri (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2023)
Raising native chickens is a business that has the potential to meet needs and provide additional family income. This livestock has quite a big role in supporting the community's economy. Free-range chicken farms that are often found in rural areas are generally traditional. Intensification of native chickens is a government activity that has been carried out since 2000 to increase the chicken population to fulfill the community's need for animal protein. The potential of native chickens can be developed by using crossbreeding, maintaining good rearing management, one of which is providing good quality and efficient food by utilizing local regional ingredients that do not compete with human needs. Results of artificial ration treatment with livestock Superior livestock produce better egg production and quality of hatching eggs as well as higher DOC weight up to 3 weeks compared to ordinary native chickens which are reared extensively with regular/traditional feed. For chicken egg production, artificial ration treatment provides better results of 35% and a growth difference of almost 50%. The positive impact of rearing like this is that apart from producing better chickens for the needs of the family/community, it can also reduce damage to yard plants and use of wasted waste.